Analysis of the Influence of Severity, Firm Size, Free Asset, and Asset Retrenchment on Corporate Turnaround in the Property & Real Estate Sector Listed on the Indonesia Stock Exchange for the Period 2020-2024 - Adhi Wichaksono; Hari Gursida; Yohanes Indrayono (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the effect of severity, firm size, free assets, and asset retrenchment on the success of corporate turnaround in Indonesian property and real estate companies experiencing negative return on assets (ROA). The study uses a quantitative approach with binary logistic regression on 21 companies selected through purposive sampling in the 2020–2024 period. Corporate turnaround is identified based on the company's ability to continuously emerge from negative ROA conditions. The test results show that severity has a negative effect on the probability of corporate turnaround success, although it is not statistically significant. Meanwhile, firm size, free assets, and asset retrenchment also had no significant effect on the success of performance recovery. These findings indicate that conventional financial indicators and ratios are not yet able to adequately explain the dynamics of corporate turnaround in the property and real estate sector, which is asset-intensive, illiquid, and highly influenced by economic cycles. This study confirms the gap between the theoretical framework based on financial indicators and the empirical reality of the property sector, and emphasizes the importance of a multidimensional approach that incorporates non-financial factors in the analysis of corporate turnaround.